Análise energética de sistemas de produção de etanol de mandioca (Manihot esculenta Crantz) - Salla, Diones A.; Furlaneto, Fernanda P. B.; Cabello, Cláudio [UNESP]; Kanthack, Ricardo A. D. (Universidade Federal da Paraíba (UFPB) Ccsa, 2010)
This work aimed to analyze the energetic consumption of the etanol production system, using the cassava as carbohidrates source. The researches were carried out from the field in the mid region of Paranapanema river, São Paulo state, during the period January to December, 2007. The energy consumption referring to the phases of crop production and industrial processing were appraised. It was verified that the total energetic cost of the crop production corresponded to 9,528.33 MJ ha(-1), and the most onerous item was the inputs (35.72%). In the industrial step, the energetic consumption was equivalent to 2,208.28 MJ t(-1). The operations of hydrolysis/saccharification/treatment of the juice represented 56.72% of the total energetic expenditure. The cassava crop presented an energetic cost of 1.54 MJ L-1 in relation to the etanol produced in the main agronomic operations crop production, and 11.76 MJ L-1 in the industrial processing. The energy efficiency observed in the cultivation and industrialization of the cassava was of 1.76.
Energetic analysis of the ethanol production systems of cassava (Manihot esculenta Crantz)
Keywords: environmental sustainability; renewable energy; agricultural production; industrial processing; carbohidrates